PERKEMBANGAN JOGET DANGKONG DI KECAMATAN MORO KABUPATEN KARIMUN PROVINSI KEPUALAUAN RIAU - Damayanti, Delvi; Astuti, Fuji (SENDRATASIK UNP, 2019)
AbstractÂ This research aims to reveal and describe the development of Joget Dangkong in Moro District, Karimun Regency, Riau Islands Province. This research was a qualitative research with analytical descriptive method. The types of data used in this research were primary and secondary data. The main instrument in this research was the researcher herself and assisted by supporting instruments such as stationeries and cameras. Data collection techniques were conducted by means of literature study, observation, interviews and documentation. The data were analyzed by data reduction, data model (data display) and conclusion drawing / verification. The results confirmed that Joget Dangkong t was one of the arts and culture that was still being developed in the Moro Subdistrict of Karimun Regency, Riau Islands Province. Therefore, it Â still exists and is accepted in the community until now. In 2019, Joget Dangkong has been developed into Joget Dangkong creations in terms of form, distribution and function, and Joget Dangkong is only performed on certain events. The response of the community was very good and very supportive in order to maintain Jogging Dangkong, because Joget Dangkong had developed from the main source to earn a living, so now it is an entertainment. The development of Joget Dangkong is possible in the midst of society to foreign countries such as Malaysia and Singapore. Joget Dangkong creation is very well responded by the community since the development of Joget Dangkong is in a positive form without violating applicable ethics and norms. Keywords: Development of Joget Dangkong